Postharvest handling of indigenous vegetables in Ghana: implications for reducing food loss and enhancing nutrition - Essilfie, G. L.; Baddoo, R. N. N.; Ayibor, S. (Frontiers in Horticulture, 2025)
Postharvest deterioration of horticultural crops, including indigenous, traditional, neglected and underutilized vegetables continues to present significant challenges across Ghana’s agricultural value chains. These crops are particularly susceptible to physiological and biochemical changes after harvest, such as moisture loss, respiration, enzymatic browning, and microbial spoilage. Inadequate postharvest handling practices and limited access to appropriate preservation technologies further exacerbate the losses due to microbial spoilage, especially among smallholder farmers and informal market actors. This study assessed the postharvest handling practices and shelf-life extension strategies employed by smallholder farmers and traders of okra, turkey berry, garden eggs, and cocoyam leaves in the Eastern, Bono East, and Ahafo regions of Ghana. A cross-sectional survey design was used, with structured interviews conducted with 270 farmers and 288 traders to document knowledge, practices, and constraints. Results revealed low overall adoption of postharvest handling technologies, although female respondents and traders demonstrated relatively higher utilization than male and farmer counterparts. Traditional preservation techniques such as sun drying were predominantly used for okra, while basic handling interventions such as cleaning, sorting, and rudimentary packaging were commonly practiced across all four crops. While drying extended shelf-life by several months, basic handling practices provided short-term quality retention, particularly for garden eggs and cocoyam leaves. Statistical analysis showed that adoption of postharvest technologies was significantly influenced by gender, education level, municipality and crop type. Key barriers identified included limited technical knowledge, inadequate infrastructure, and high implementation costs. The study highlights the need for targeted capacity-building initiatives, investment in appropriate postharvest infrastructure, and collaborative engagement with stakeholders to promote appropriate preservation technologies. Strengthening postharvest handling systems for indigenous vegetables has the potential to extend shelf life, reduce postharvest losses, enhance food availability, and contribute to improved nutrition among Ghanaian consumers.